Epidemiology of injuries in National Collegiate Athletic Association women's tennis: 2014-2015 through 2018-2019 - Robison, H. J.; Boltz, A. J.; Morris, S. N.; Collins, C. L.; Chandran, A. (Journal of Athletic Training, 2021)
Context: The National Collegiate Athletic Association (NCAA) has sponsored women's tennis programs since 1966. Women's tennis has risen in global prominence and popularity within the NCAA. Background: Continued surveillance of athletic injuries in the NCAA is critical for identifying emerging injury trends and assessing injury prevention strategies. Methods: Exposure and injury data collected in the NCAA Injury Surveillance Program from 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 4.16 per 1000 athlete exposures. Injury to the shoulder, foot, and trunk were the most prevalent throughout the study period. Approximately 30% of all injury diagnoses were related to inflammatory conditions. Also, 32.1% of all injuries were time-loss injuries, and 45.0% of all injuries were non-time-loss injuries. Conclusions: The findings of this study differed slightly from those of previous investigations, most notably with regard to injury rate by season segment and commonly injured body parts. Future surveillance efforts should attempt to capture the nuances of tennis competitions.